The Evaluation of the Pharmaceutical Planning and Procurement System at Pharmacies in Western Semarang District - Gloria, Fransisca; Al Farizi, Gilang Rizki; Addini, Belkis Nur (STIKES Telogorejo Semarang, 2022)
Pharmaceutical planning and procurement become important matters for medicine management at pharmacies. The inaccurate plan leads to budget extravagances of medicine procurement, procurement cost, overloaded medicine supply, and lack of medicine supply. Ineffective procurement led to limited medicine supplies in terms of the amount and the correct price. This research evaluated the pharmaceutical matter plan and procurement at pharmacies in Western Semarang District. This descriptive research used a cross-sectional design so this research was also non-experimental research with a qualitative approach. The data collecting technique was direct observation of the pharmaceutical plan and procurement system from various conventional pharmacies in the Western Semarang area. The results obtained from 5 pharmacies showed an average mean percentage of 91.43%. On the other hand, the average mean percentage of procurement was 85.45%. These results were categorized as